2011
DOI: 10.3168/jds.2010-3277
|View full text |Cite
|
Sign up to set email alerts
|

Differing effects of 2 active dried yeast (Saccharomyces cerevisiae) strains on ruminal acidosis and methane production in nonlactating dairy cows

Abstract: Fifteen ruminally cannulated, nonlactating Holstein cows were used to measure the effects of 2 strains of Saccharomyces cerevisiae, fed as active dried yeasts, on ruminal pH and fermentation and enteric methane (CH(4)) emissions. Nonlactating cows were blocked by total duration (h) that their ruminal pH was below 5.8 during a 6-d pre-experimental period. Within each block, cows were randomly assigned to control (no yeast), yeast strain 1 (Levucell SC), or yeast strain 2 (a novel strain selected for enhanced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 31 publications
5
88
1
1
Order By: Relevance
“…Similar to the temperature results, Thrune et al (2009) reported greater mean ruminal pH and less time spent under a pH threshold of 5.6 with live yeast supplementation. Similarly, Chung et al (2011) reported that time spent below pH of 5.8 was numerically reduced using the same live yeast strain as used in the present study. Saccharomyces cerevisiae has been shown to create a more anaerobic environment through oxygen scavenging (Newbold et al, 1996), as well as provide growth factors (including organic acids, B vitamins, and AA) that stimulate microbial growth, particularly lactate utilizers (Chaucheyras-Durand et al, 2008).…”
mentioning
confidence: 73%
“…Similar to the temperature results, Thrune et al (2009) reported greater mean ruminal pH and less time spent under a pH threshold of 5.6 with live yeast supplementation. Similarly, Chung et al (2011) reported that time spent below pH of 5.8 was numerically reduced using the same live yeast strain as used in the present study. Saccharomyces cerevisiae has been shown to create a more anaerobic environment through oxygen scavenging (Newbold et al, 1996), as well as provide growth factors (including organic acids, B vitamins, and AA) that stimulate microbial growth, particularly lactate utilizers (Chaucheyras-Durand et al, 2008).…”
mentioning
confidence: 73%
“…This result is in agreement with a previous study that Saccharomyces cerevisiae reduces ruminal CH 4 production (Lynch and Martin, 2002), but others found no effect (Lila et al, 2004) or an increase (Martin et al, 1989) in batch cultures with mixed rumen microflora. The discrepancies among studies could be associated with the characteristics of the strain (Chuang et al, 2011), diet composition (Sullivan and Martin, 1999) and dose (Lila et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Although this relationship holds in some studies (e.g., Chung et al, 2011;Van Zijderveld et al, 2010), treatment effects on CH 4 emissions and VFA proportions did not correspond in about half of the studies (e.g., Beauchemin et al, 2009;Brask et al, 2015;Supplementary Table S1; https://doi.org/10.3168/jds.2016-12030). Overall, the relations between CH 4 emission and both VFA and pH are variable in the literature and not as straightforward as expected from theory.…”
Section: Rumen Ph and Vfamentioning
confidence: 99%